Candida auris exhibits resilient biofilm characteristics in vitro: implications for environmental persistence. Issue 1 (September 2019) - Short, B.; Brown, J.; Delaney, C.; Sherry, L.; Williams, C.; Ramage, G.; Kean, R.
Summary: Surfaces within healthcare play a key role in the transmission of drug-resistant pathogens. Candida auris is an emerging multidrug-resistant yeast which can survive for prolonged periods on environmental surfaces. Here we show that the ability to form cellular aggregates increases survival after 14 days, which coincides with the upregulation of biofilm-associated genes. Additionally, the aggregating strain demonstrated tolerance to clinical concentrations of sodium hypochlorite and remained viable 14 days post treatment. The ability of C. auris to adhere to and persist on environmental surfaces emphasizes our need to better understand the biology of this fungal pathogen.